Gaya Kepemimpinan Berimplikasi Terhadap Kinerja Guru di SMP Negeri 2 Panumbangan Ciamis - Yayan Rudianto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2023)
ABSTRACT The teacher is a professional educator with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education, formal education, basic education and secondary education. Teachers are considered professional if they are the same or more productive at work. To achieve this, it is necessary to conduct a performance appraisal. Not infrequently the teacher's performance still does not meet predetermined work standards, such as a lack of discipline, the application of learning models that are less effective, the learning process in the classroom is less attractive so that students tend to have difficulty developing their best abilities. Even though professional and qualified teachers are recognized by their own qualifications. In this regard, one of the factors that influence teacher performance is leadership, especially the principal's leadership style which has implications for teacher performance. However, whether this influence effort is successfully carried out by school principals still needs to be studied and analyzed more deeply in order to find out how and to what extent the principal's leadership style has implications for teacher performance. The method used is descriptive quantitative. The population is 30 people who are teachers at SMPN 2 Panumbangan. The technique of determining the sample size using the census method. The data used is primary data obtained by distributing questionnaires directly to respondents. The results of simple linear regression analysis show that the principal's leadership style has positive and significant implications for teacher performance. Keywords: Leadership Style, Teacher Performance